Inovasi Kewirausahaan Digital: Strategi Adaptasi UMKM di Era Ekonomi Kreatif - Novariani Indri Utami; Feri SW (IAI Nasional Laa Roiba Bogor, 2025)
The rapid development of digital technology has driven significant transformation in the business landscape, particularly for Micro, Small, and Medium Enterprises (MSMEs). In the era of the creative economy, digital entrepreneurship innovation has become a key strategy to enhance competitiveness and sustainability. This study aims to analyze the forms of digital innovation adopted by MSME actors and to identify effective adaptation strategies in facing the challenges and opportunities of digitalization. This research employs a qualitative descriptive method through in-depth interviews and observations of MSME players in the creative industry sector. The findings reveal that the utilization of digital platforms such as social media, online marketplaces, and digital payment systems significantly improves market reach, operational efficiency, and customer engagement. Furthermore, successful adaptation strategies include increasing digital literacy, collaborating with digital communities, and developing market-driven product innovations. These findings emphasize that digital entrepreneurship innovation is a critical foundation for the resilience and growth of MSMEs within an ever-evolving creative economy ecosystem.